Implementation of the Use of Digital Marketing as a Strategy to Strengthen Technopreneurship Resources - Victor Oghenenyerovwome Iki (Community Service Akseprin Journal, 2024)
Micro enterprises have a real contribution in economic growth in every region. It is necessary to strengthen the competence  of business resources in the  use of digital technology as an effort to grow technopreneurship, in the face of global competitiveness demands. To develop these competencies, skills, expertise, innovation and creativity are needed in the use of digital marketing platforms. However, there are still business actors who are not adaptive to these competencies. Community Service activities are expected to provide solutions to these problems in the form of skills counseling activities for the use of various digital marketing platforms with offline exposure, discussion and question and answer methods as well as simulations. Based on the results of the evaluation, the activity went well and the training material was in accordance with work needs. The follow-up needs a sustainability program with assistance to build technopreneurship and togetherness between business communities  through the media of the Information/Communication Forum